2005
DOI: 10.1007/s00424-005-1515-2
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric effects of external K+ ions mediated by the aspartate of the GYGD signature sequence in the Kv2.1 K+ channel

Abstract: K+ channels achieve exquisite ion selectivity without jeopardizing efficient permeation by employing multiple, interacting K+-binding sites. Introduction ofa cadmium (Cd2+)-binding site in the external vestibule of Kv2.1 (drk1), allowed us to functionally characterize a binding site for external monovalent cations. Permeant ions displayed higher affinity for this site than non-permeant monovalent cations, although the selectivity profile was different from that of the channel. Point mutations identified the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…High affinity permeant ions like Rb + and Cs + (which interact intimately with the selectivity filter) slow down the closure of the internal gate of many K + channels4,16,17. Mutations at or near the selectivity filter lead to a variety of gating effects in K + channels11,18,19,20, while block by the N-terminal inactivating particle, which tends to lock open the inner gate, greatly accelerates entry into the C-type inactivated state3. Experiments on Kir 1.1 have shown that gating by either intracellular protons or extracellular K + ions appear to be coupled through conformational changes near the selectivity filter21.…”
mentioning
confidence: 99%
“…High affinity permeant ions like Rb + and Cs + (which interact intimately with the selectivity filter) slow down the closure of the internal gate of many K + channels4,16,17. Mutations at or near the selectivity filter lead to a variety of gating effects in K + channels11,18,19,20, while block by the N-terminal inactivating particle, which tends to lock open the inner gate, greatly accelerates entry into the C-type inactivated state3. Experiments on Kir 1.1 have shown that gating by either intracellular protons or extracellular K + ions appear to be coupled through conformational changes near the selectivity filter21.…”
mentioning
confidence: 99%
“…The identity of the residue immediately following the second glycine of the selectivity filter motif affects conductance and rectification as well as gating, binding of K + and potency of inhibitors [66], [67]. An aspartate residue at this locus reduces block by Cd 2+ [68] and tetraethylammonium (TEA) [66], suggesting that sensitivity to these and other blockers may differ between GYGD-containing human K + channels and the GYG S -containing protozoan K + channel homologues. These GYG S -containing parasite channels also contain a glutamate residue at an analogous position to the conserved P-loop glutamate residue of K ir channels and KcsA (E138 in K ir 2.1, Figure 2 ) that is involved in gating at the selectivity filter [69], [70].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is a clear correlation between the occurrence of sub-conductance levels with altered selectivity and mutations in the selectivity filter (Chapman et al, 1997;Zheng and Sigworth, 1997). Mutations at the selectivity filter (Lu et al, 2001) or surrounding structure (Alagem et al, 2003;Chapman et al, 2006;Proks et al, 2001;Sun et al, 1996), showed dramatic effects on rapid gating transitions, while others revealed a large influence in the kinetics and extent of C-type inactivation. Moreover, increasing K + concentration or binding of the blocker TEA in the extracellular region leads to dramatic decrease of C-type inactivation (Baukrowitz and Yellen, 1995;Choi et al, 1991;Lopez-Barneo et al, 1993).…”
Section: 44 Engineering Hydrogen-bond Network In Kv Potassium Channelsmentioning
confidence: 99%
“…Similarly, numerous studies support the role of a network of hydrogen bond interactions behind the selectivity filter during channel gating in a number of K + channels (Kurata and Fedida, 2006;Seebohm et al, 2003). A point mutation in Kv2.1 (D378E, from the GYGD), affects the single channel behavior by the destabilization of the open state (Chapman et al, 2006). Moreover, mutations in the selectivity filter and pore helix of Shaker, hERG, and inward rectifiers also have large effects on gating properties (Alagem et al, 2003;Ficker et al, 1998;Yifrach and MacKinnon, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation